2023
DOI: 10.3389/fmed.2023.1111315
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone, cerclage, pessary, or acetylsalicylic acid for prevention of preterm birth in singleton and multifetal pregnancies – A systematic review and meta-analyses

Abstract: BackgroundPreterm birth is the leading cause of childhood mortality and morbidity. We aimed to provide a comprehensive systematic review on randomized controlled trials (RCTs) on progesterone, cerclage, pessary, and acetylsalicylic acid (ASA) to prevent preterm birth in asymptomatic women with singleton pregnancies defined as risk of preterm birth and multifetal pregnancies.MethodsSix databases (including PubMed, Embase, Medline, the Cochrane Library) were searched up to February 2022. RCTs published in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 140 publications
0
2
0
1
Order By: Relevance
“…Some of the studies used in this analysis included a variety of risk factors for preterm birth, such as maternal age and smoking. These risk factors did not appear to have the same predictive value as other risk factors, such as history of previous preterm birth and presence of abnormalities in the uterus, so a subsequent statistical analysis was performed in this study and found that the results of the analysis were still the same even after exclusion of Watson's study that included smoking in older women in risk factors [24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Some of the studies used in this analysis included a variety of risk factors for preterm birth, such as maternal age and smoking. These risk factors did not appear to have the same predictive value as other risk factors, such as history of previous preterm birth and presence of abnormalities in the uterus, so a subsequent statistical analysis was performed in this study and found that the results of the analysis were still the same even after exclusion of Watson's study that included smoking in older women in risk factors [24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 83%
“…The cervical threshold under which the cervix was considered to be short was set at 25 mm, predicting with high sensitivity the risk of premature birth below 35 weeks of gestation, while women with a prior history of preterm labor and cervical surgery were identified as high risk for preterm labor. It was also found that the likelihood of preterm birth below 35 weeks is less in cases where cervical length < 25 mm is measured at 20-24 weeks of gestation, than the likelihood of preterm labor in cases where cervical length < 25 mm is measured at a gestational age less than 20 weeks or more than 24 weeks [20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Para gestantes com gestação única e de alto risco de parto pré--termo (seja por história de parto pré-termo espontâneo anterior e/ ou colo curto ao US), deve ser oferecido o uso da progesterona para prevenção da prematuridade 1,48,49 . O benefício do uso da progesterona é mais significativo nas gestantes com história prévia de parto pré--termo espontâneo e colo curto.…”
Section: Progesteronaunclassified